2018
DOI: 10.1128/iai.00331-18
|View full text |Cite
|
Sign up to set email alerts
|

Genome Plasticity of agr -Defective Staphylococcus aureus during Clinical Infection

Abstract: Therapy for bacteremia caused by Staphylococcus aureus is often ineffective, even when treatment conditions are optimal according to experimental protocols. Adapted subclones, such as those bearing mutations that attenuate agr-mediated virulence activation, are associated with persistent infection and patient mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 93 publications
(109 reference statements)
6
39
1
Order By: Relevance
“…Inversions were much more frequent in CC5 and USA100, which may reflect higher similarity between endogenous prophages and/or the increased divergence between isolates in the USA100 lineage. Most inversions could only be resolved by long-read sequencing data, and our results, combined with our previous observations among MSSA isolates (Altman et al 2018) , suggest that prophage-mediated recombinations may be more frequent than previously appreciated. Indeed, one inversion event occurred in the outbreak clone during the spread from the adult wards to the NICU.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Inversions were much more frequent in CC5 and USA100, which may reflect higher similarity between endogenous prophages and/or the increased divergence between isolates in the USA100 lineage. Most inversions could only be resolved by long-read sequencing data, and our results, combined with our previous observations among MSSA isolates (Altman et al 2018) , suggest that prophage-mediated recombinations may be more frequent than previously appreciated. Indeed, one inversion event occurred in the outbreak clone during the spread from the adult wards to the NICU.…”
Section: Discussionsupporting
confidence: 70%
“…PacBio SMRT sequencing data were assembled using a custom genome assembly and finishing pipeline (Altman et al 2018) . Briefly, sequencing data was first assembled with HGAP3 version 2 · 2 · 0 (Chin et al 2013) .…”
Section: Complete Genome Assembly and Finishingmentioning
confidence: 99%
“…We prepared sequencing libraries from DNA extracted from each MRSA isolate as previously described (24,96). Whole-genome sequencing was performed using Illumina HiSeq 2000 with 100-base paired-end reads or a PacBio RSII instrument (24,49,96). Paired-end Illumina reads were mapped against USA300_FPR3757 reference genome using Burrows-Wheeler Aligner (BWA) (97).…”
Section: Discussionmentioning
confidence: 99%
“…Altman and coworkers have shown that within-host loss of agr function was associated with increased genetic divergence between distinct S. aureus subclones 44 . In synthesis, whereas agr dysfunction is adaptive for survival in the infected bone, it may be counter adaptive outside such niche.…”
Section: Discussionmentioning
confidence: 99%
“…In the present report we show that S. aureus can regain CP production when subjected to selection pressure in vivo through a mechanism that does not require RNAIII expression. Indeed, in a previous study it has been shown that genetic changes occurring in an agr-defective infecting S. aureus strain resulted in increased virulence in a murine model of bloodstream infection thus bypassing the agr mutation 44 . The S. aureus derivative obtained after passage through the bloodstream displayed a significant reduction in the capacity to trigger TNFα production and became less adapted to bone as ascertained by its decreased capacity to induce osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%